DTI and MTR Measures of Nerve Fiber Integrity in Pediatric Patients With Ankle Injury - Holmes, Scott A.; Karapanagou, Anastasia; Staffa, Steven J.; Zurakowski, David; Borra, Ronald; Simons, Laura E.; Sieberg, Christine; Lebel, Alyssa; Borsook, David (Frontiers in Pediatrics, 2021)
Acute peripheral nerve injury has the potential to lead to chronic neuropathic pain. Having a standardized, non-invasive method to evaluate pathological changes in a nerve following nerve injury would help with diagnostic, prognostic and therapeutic opportunities. In addition, the accurate evaluation of nerve fiber integrity after injury may provide insight into the extent of pathology as well as potential dissociation between the extent of pathology and a patient’s level of self-reported pain. The aim of this investigation was to evaluate the extent to which peripheral nerve integrity could be evaluated in an acute ankle injury cohort and how nerve fiber integrity correlates with self-reported pain levels in afferent nerves (sciatic and its two major contributors, fibial and tibial nerves, innervating the lateral and medial components of the ankle respectively). We recruited 39 pediatric participants with clinically defined neuropathic pain within 3 months of an ankle injury and 16 healthy controls. Participants underwent peripheral nerve imaging using diffusion tensor (DTI) and magnetization transfer ratio imaging of their injured and non-injured ankles. The imaging window was focused on the branching point of the sciatic nerve into the tibial and fibular division. Each participant completed the Pain Detection Questionnaire (PDQ). Findings demonstrated group differences in nerve fiber integrity in the sciatic, tibial and fibular nerve in the injured ankle relative to healthy control and contralateral non-injured nerve fibers. The only metric of nerve fiber integrity to correlate with pain reporting was MTR in the right fibular nerve. Pain reporting correlated with time since injury and may shed light on a sub-acute timeframe of nerve fiber pathology. Findings from this investigation underscore the value of peripheral nerve fiber imaging to show evidence of altered nerve fiber integrity and its dissociation from reported pain levels. Such changes may be the harbinger of future chronic pain that occurs months to years after the injury. Future research should emphasize sub-acute time frames of injury to capture post injury inflammation and stages of nerve fiber recovery.